Compound‐specific δ13C analyses reveal sterol metabolic constraints in an aquatic invertebrate. (25th August 2015) - Gergs, René; Steinberger, Nicole; Beck, Birgit; Basen, Timo; Yohannes, Elizabeth; Schulz, Ralf; Martin‐Creuzburg, Dominik
<x xml:space="preserve">Abstract</x> Rationale Dietary sterol deficiencies can have severe life history consequences for consumers. Compound‐specific stable isotope analysis (CSIA) was applied to the exploration of the sterol metabolic constraints and bioconversion capacities of the amphipod Gammarus roeselii. Evaluating structural sterol requirements has great potential to improve our understanding of the ecological relevance of sterols as limiting nutrients. Methods Juvenile G. roeselii were reared on food mixtures consisting of different ratios of the two algae Scenedesmus obliquus (cultivated with 13C‐labeled NaHCO3) and Nannochloropsis limnetica (unlabeled), which have been shown previously to differ in food quality. We measured the sterol content and composition using a gas chromatograph equipped with a flame ionization detector and the δ13C values of sterols using compound‐specific isotope ratio mass spectrometry to examine potential sterol‐mediated nutritional constraints of G. roeselii. Results In the food mixtures, δ13C values of cholesterol, synthesized by N. limnetica, were −25‰ and those of the Δ7‐phytosterols, chondrillasterol and fungisterol, synthesized by S. obliquus, were 7 and 18‰, respectively. Although the cholesterol concentrations in G. roeselii decreased with increasing proportion of dietary S. obliquus, the δ13C values remained constant at −25‰. Lathosterol, which appeared in G. roeselii at high dietary proportions of S. obliquus, had a δ13C value of 35‰. Conclusions We provide evidence that the the Δ7‐phytosterols present in S. obliquus cannot be metabolized to cholesterol in G. roeselii, resulting in the accumulation of lathosterol in the animals and potentially in sterol‐limited growth. These findings emphasize the advantage of CSIA in revealing the physiological mechanisms associated with nutritional constraints. Copyright © 2015 John Wiley & Sons, Ltd.